Tereza Batista cansada de guerra: a resistência à violência e à opressão feminina - REGO, Francisca Magnólia de Oliveira (Universidade Federal do Pará, 2018)
It is known that, working as a mirror reflecting relations in society, the literature has perpetuated over the years, profiles of women stereotyped according to the precepts of patriarchal society that frame the model of submission, walling and silence. Whereas in the twentieth century, especially in the 60s and 70s, the feminist movement brought about the emancipation of women, this dissertation aimed to investigate how gender issues are portrayed in the fiction of Jorge Amado, whose centerpiece is the woman in this case particular, the work Tereza Batista Tired of War. Therefore, it was essential to support the theories that address the study of females and their representations, as well as in texts dedicated to the critical work of Jorge Amado. Along the way, started with a literature search on the author and his literary creations and representations of women in Brazilian literature, the data were put together in order to get the nuances that are important to building the profile of Tereza Batista, in intended to reveal the extent to which the literary text busted and highlights social situations as a way to denounce the violence and oppression against women.